KADAR MDA DAN RASIO GSH/GSSH PADA KEHAMILAN NORMAL,PREEKLAMPSIA BERAT DAN EKLAMPSIA DI MALANG - Candra, Siti; Widodo, M Aris; Suwarto, Soetomo; Muliartha G, I Ketut (Jurnal Kedokteran Brawijaya, 2007)
Preeclampsia is marked by vasospasme, increasing peripheral vascular resistance and permeability, endothelial cell and reducing organ perfusion. It occurs because of the increasing of lipid hydroperoxides. The uncontrolled production of lipid hydroperoxides causes oxidative stress and destroyscell integrity. Oxidative stress condition expressthe increasing oxidant and decreasing antioxidant. One of the antioxidant is GSH that is used to neutralize the increasing of Malondialdehyde (MDA) level. The objective of this study was to see the difference of MDA content and GSH. GSSG ratio between the normal pregnancy, preeclamsia and eclampsia. This study was cross sectional study. The samples were 36 blood plasma consisted of 12 normal pregnancy, 12 preeclampsia and 12 eclampsia before birth. The bloodplasma, was measured for its MDA level and the GSH/GSSH ratio.The result showed that the level of MDA of plasma in preeclamptic and eclamptic pregnancy were higher than normal pregnancy p=0.000, due to lipid peroxidation resulted  from increased production of lipid hydroperoxides on preeclamptic  and eclamptic pregnancy.